Cycling Performance Enhancement After Drop Jumps May Be Attributed to Postactivation Potentiation and Increased Anaerobic Capacity - de Poli, Rodrigo A B [UNESP]; Boullosa, Daniel A.; Malta, Elvis S. [UNESP]; Behm, David; Lopes, Vithor H F [UNESP]; Barbieri, Fabio A. [UNESP]; Zagatto, Alessandro M. [UNESP] (Wolters Kluwer, 2020)
de Poli, RAB, Boullosa, DA, Malta, ES, Behm, D, Lopes, VHF, Barbieri, FA, and Zagatto, AM. Cycling performance enhancement after drop jumps may be attributed to postactivation potentiation and increased anaerobic capacity. J Strength Cond Res 34(9): 2465-2475, 2020-The study aimed to investigate the effects of drop jumps (DJs) on supramaximal cycling performance, anaerobic capacity (AC), electromyography, and fatigue. Thirty-eight recreational cyclists participated into 3 independent studies. In study 1 (n = 14), neuromuscular fatigue was assessed with the twitch interpolation technique. In study 2 (n = 16), the AC and metabolic contributions were measured with the maximal accumulated oxygen deficit method and the sum of the glycolytic and phosphagen pathways. In study 3 (n = 8), postactivation potentiation (PAP) induced by repeated DJs was evaluated. The DJ protocol was effective for significantly improving cycling performance by +9.8 and +7.4% in studies 1 and 2, respectively (p ≤ 0.05). No differences were observed in electromyography between conditions (p = 0.70); however, the force evoked by a doublet at low (10 Hz) and high frequencies (100 Hz) declined for control (-16.4 and -23.9%) and DJ protocols (-18.6 and -26.9%) (p < 0.01). Force decline was greater in the DJ condition (p < 0.03). Anaerobic capacity and glycolytic pathway contributions were +7.7 and +9.1% higher after DJ protocol (p = 0.01). Peak force during maximal voluntary contraction (+5.6%) and doublet evoked force at 100 Hz (+5.0%) were higher after DJs. The DJ protocol induced PAP, improved supramaximal cycling performance, and increased AC despite higher peripheral fatigue.